STUDI KOMPARASI PRESTASI BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) DENGAN NUMBERED HEADS TOGETHER (NHT) PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR DI KELAS X SMA NEGERI 2 DAYUN - Fahdila Engraini; R. Usman Rery; Abdullah ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research about comparing cooperative learning models types Two Stay Two Stray (TSTS) with Numbered Head Together (NHT) has been done to improve student’s achievement on learning topic Atomic structure and periodic systems of elements at class X SMAN 2 Dayun. This research aimed to find out student’s achievement the better one between cooperative learning models types Two Stay Two Stray (TSTS) with Numbered Head Together (NHT) on learning topic of Atomic structure and periodic systems of elements by comparing these two models. This was a quasi experimental research with pretest-posttest design. Population on this research ware all classes X in SMAN 2 Dayun consisting of four classes. The subject of this research ware X4 as the experimental class of TSTS and X2 as the experimental class of NHT, which were determined randomly after conducting normality and homogeneity test. The data analysis to test the hypothesis was using two tail t-test. Based on the data analysis, it is obtained that tcount = 4,271 and ttable = 2,00 with α = 0,05, dk = 53. tcount ≥ ttable 4,271≥ 2,00. It means there are significant differences between the student’s achievement by using cooperative learning model type Two Stay Two Stray (TSTS) with the student’s achievement by using cooperative learning model type Numbered Head Together (NHT) on the learning topic of Atomic structure and periodic systems of elements in SMAN 2 Dayun.Keywords: TSTS, NHT, Learning achievement, Atomic structure and periodic systems of elements